Influence of economic freedom and its subcomponents on risk-taking behavior Evidence from dual banking system of Malaysia - Harkati, Rafik; Syed Jaafar Alhabshi, Syed Musa; Kassim, Salina (Emerald Group Publishing Ltd., 2020)
The purpose of this paper is to investigate the influence of economic freedom and six relevant sub-components of it on the risk-taking behavior of banks in the Malaysian dual banking system. It also aims to make a comparative analysis between Islamic and conventional banks operating in this dual banking sector. Moreover, the study is an effort to enrich the existing literature by presenting empirical evidence on the argument that the risk-taking behavior of the two types of banks is indistinguishable given that they operate in the same regulatory environment. Secondary data of all banks operating in the Malaysian banking sector are collected from FitchConnect database, in addition to the economic freedom index from Foundation Heritage for the period 2011–2017. Generalized least squares technique is employed to estimate the influence of economic freedom and the six relevant subcomponents of it on the risk-taking behavior of banks. Findings – The level of economic freedom influenced risk-taking behavior within the banking sector as a whole, conventional and Islamic banking sectors negatively during the study period (2011–2017). Risk-taking behavior of conventional and Islamic banks is similar. However, conventional banks turn to be less influenced by economic freedom level as compared to Islamic banks. The government and regulators may benefit from the results by rethinking and setting the best economic freedom index that better serves the stability of the banking system, and lessens banks’ risk-taking inclination. To the present time, this paper is thought to be of a significant contribution. Given the argument that Islamic and conventional banks behave in the same way. This is one of the first attempts to address this issue in light of the influence of economic freedom and six sub-components of it on the risk-taking behavior of banks operating in a dual banking system.